Research on Remote Control System of Excavator Based on Cloud Platform - Ran Liu; Zhiguang Guan; Zhenyuan Zhao; Qin Sun (Journal of Applied Science and Engineering)
Excavators are increasingly used across various industries, especially in dangerous environments such as mines, earthquake relief sites, and more. In these hazardous settings, the personal safety of excavator operators cannot be fully guaranteed. However, the implementation of remote control for excavators can effectively mitigate the risks associated with human operation on-site, thereby enhancing workers’ safety and operational efficiency. The excavator remote control system presented in this paper offers significant improvements compared to traditional excavator control systems, including (1) the realization of unlimited-distance remote control through the intervention of an IoT cloud server and (2) the accomplishment of semi-automatic and autonomous excavator operation via a binocular vision system. Experimental results demonstrate that the cloud-based excavator control system achieves remote control with low latency and high reliability, enabling functions such as walking, steering, and the extension of boom, stick, and bucket.